Design of digital signal processor - Teo, Siaw Hui. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Digital signal processing (DSP) is concerned with t he representation of the signals by a sequence of numbers and the processing of these signals. A simple digital signal processor could be constructed from blocks like arithmetic logic unit (ALU), multiply-accumulator (MAC), multiplier and s hifter. Thus, this project is carried out to combine those blocks and design the processing datapath for Universal Serial Bus with less logic utilization or small are a. The architecture of DSP is constructed and translates into VHDL source code. In designing, critical path for each block are reduced as much as possible to minim um the delay. Digital signal processing often process data using fixed-point ari thmetic, although some applications are available to use floating point ar ithmetic which is more powerful depending on the design. Logic function offers a s olution for the computationally- intensive found in digital signal processing. There fore, programmable logic can provide increased DSP system performance at reduced system cost. So, a cheaper price but higher performance USB interface devices could be created for the convenient of data transfer.